The mediating effect of tacit knowledge sharing in predicting innovative behaviour from trust - Justin Wah, Nur Constance Rinen; Zawawi, Dahlia; Raja Yusof, Raja Nerina; Sambasivan, Murali; Karim, Jalina (Universiti Malaysia Sarawak, 2018)
The main purpose of this research is to examine a mediating effect understanding of tacit knowledge sharing on both affect and cognition-based trust with innovative behaviour in a Malaysian public teaching hospital. A quantitative method approach within a post-positivist paradigm using questionnaire was employed to gather data for the study and analyses were performed using Structural Equation Modelling (SEM) which confirmed using partial least square (PLS). The results of analysing339 nurse –nurse supervisor dyads revealed that tacit knowledge sharing mediates the relationship between affect and cognition-based trust with innovative behaviour. In the future, more research on Malaysian teaching hospitals is needed to explore the willingness to share tacit knowledge. This study pointed out that supervisor in a teaching hospital may need to use this finding in developing ways to ensure innovative behaviour is practice efficiently among the nurses. This study adds to the body of knowledge about the effect of tacit knowledge sharing on trust and innovative behaviour of nursing employees.